Per una proposta di studio dei cataloghi in Tucidide - Stigliano, Riccardo (Histos, 2026)
This paper analyses Thucydides’ catalogues both as a narrative and analytical device within The Peloponnesian War. In particular, this study aims to show their authenticity or functional coherence and cohesion despite the fact that they have been understudied or not always fully understood to varying degrees. Through this close examination, I illustrate how Thucydides adapts the traditional catalogue structure and patterns (ethno-geographic or political-hierarchical) to serve his new kind of historiography. By slightly echoing Homeric and Herodotean models, the author innovates within the catalogic sub-genre, highlighting political alliances, military logistics, and imperial dynamics in the war he is recounting.